The influence of ethanol-diesel blend on pollutant emissions from different bus fleets under acceleration transitions. (1st December 2017) - Mata, Carmen; Gómez, Arántzazu; Armas, Octavio
Highlights: The effect of ethanol-diesel (ED) fuel blend was studied under accelerations of urban buses. At high altitude the ED fuel reduces NOx due to the high enthalpy of vaporization of fuel. At low altitude the ED fuel reduced particles and increased NOx due to the high air oxygen availability. The altitude clearly modifies the trade-off NOx-particles even when the ED fuel is used. Abstract: Main pollutant emissions produced by urban diesel buses are nitrogen oxides and particulate matter. Moreover, it is well known that level of emissions produced under real world driving conditions can be very different compared to those obtained under dyno-chassis tests or engine tests. The causes of these differences can be due to several sources such as operating conditions at various temperatures and pressures, different ground roughness, slopes, driver effect, change of gears or traffic. This work studies the effect of two different fuels on nitrogen oxides and particle size distributions under real world driving sequences of vehicle acceleration. Fuels tested were a low sulfur Diesel fuel (without biodiesel) and a binary ethanol–diesel fuel blend. This work was done with two models of similar buses, each one operating in cities located at different altitudes. Results show a reduction in particle concentration when ethanol-diesel blend was used. Mean geometric diameters decreased when ethanol-diesel was used. Concerning nitrogen oxides emissions, different trends were observed between vehicles depending on the transient sequence and the fuel used. Ethanol-diesel fuel blend reduces NOx at high altitude, but increases at low altitude. All results were probably affected by the altitude of the cities more than by the vehicle model itself.